PERAN MEDIASI AUDIT TENURE ANTARA UMUR PERUSAHAAN, UKURAN PERUSAHAAN TERHADAP AUDIT DELAY: PERAN MEDIASI AUDIT TENURE ANTARA UMUR PERUSAHAAN, UKURAN PERUSAHAAN TERHADAP AUDIT DELAY - Bambang Widjanarko Susilo; Edy Susanto; Ayu Miranti Kusumaningrum; Febryantahanuji Febryantahanuji; Zahra Dinul Khaq; Galuh Aditya; Risma Nurhapsari (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2024)
The purpose of the study is to determine and test whether partially the size of the company, the age of the company, is significant to the audit tenure and audit delay and also to test whether the audit tenure is able to mediate the effect of reducing the effect of the relationship between company size, company age and audit delay. Secondary quantitative financial statements of 48 Indonesia Stock Exchange companies in the property and real estate sector. Samples were obtained by 48 companies by purposive sampling. Analysis with path analysis software SPSS v24. The company's age results are the only significant variable to audit delay. While audit tenure, partial company size is not significant to audit delay, and audit tenure cannot increase influence as an intervening variable.